ERRATUM: ERRATUM - Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2024)
Erratum to:Hartati S, Meliansyah R, Mayanti T. 2024. Potensi Senyawa Volatil dari Khamir untuk Mengendalikan Cercospora coffeicola. Jurnal Fitopatologi Indonesia. 20(1):1-16. DOI: https://doi.org/10.14692/jfi.20.1.1-14.Fauziyah Q, Ramdan EP, Risnawati R, Yulianti F. 2024. Perlakuan Panas Kering dan Ekstrak Rimpang Lengkuas terhadap Benih Kedelai Terinfeksi Xanthomonas axonopodis. Jurnal Fitopatologi Indonesia. 20(1):17-25. DOI: https://doi.org/10.14692/jfi.20.1.15-23.Kurniawati F, Supramana, Hidayat SH, Tondok ET, Syafutra H. 2024. Perbanyakan Nematoda Daun Aphelenchoides fragariae pada Biakan Cendawan. Jurnal Fitopatologi Indonesia. 20(1):26-33. DOI: https://doi.org/10.14692/jfi.20.1.24-31. In the original version of this article, the title and caption for tables and figures were only in written Indonesian. A change of style has been made to all tables and figures, with adding a titles and captions in English. Furthermore, there are changes to the page numbers as follows:The page number for the article Hartati S, Meliansyah R, Mayanti T. 2024. Potensi Senyawa Volatil dari Khamir untuk Mengendalikan Cercospora coffeicola. Jurnal Fitopatologi Indonesia. 20(1):1-16. DOI: https://doi.org/10.14692/jfi.20.1.1-14 written "1-14" is changed to "1-16".The page number for the article Fauziyah Q, Ramdan EP, Risnawati R, Yulianti F. 2024. Perlakuan Panas Kering dan Ekstrak Rimpang Lengkuas terhadap Benih Kedelai Terinfeksi Xanthomonas axonopodis. Jurnal Fitopatologi Indonesia. 20(1):17-25. DOI: https://doi.org/10.14692/jfi.20.1.15-23 written “15-23” is changed to “17-25”.The page number for the article Kurniawati F, Supramana, Hidayat SH, Tondok ET, Syafutra H. 2024. Perbanyakan Nematoda Daun Aphelenchoides fragariae pada Biakan Cendawan. Jurnal Fitopatologi Indonesia. 20(1):26-33. DOI: https://doi.org/10.14692/jfi.20.1.24-31 written “24-31” is changed to “26-33”The correction has been made on the website and in the PDF version of the article.